A characterization of the family of iterated nonexpansive mappings under every renorming - Pérez-García, Víctor; Castillo-Santos, Francisco Eduardo (Topological Methods in Nonlinear Analysis, 2024)
We characterize the family of iterated nonexpansive mappings that are stable under every renorming. The family of iterated nonexpansive mappings contains the family of nonexpansive mappings, it also contains quasi-nonexpansive and Suzuki’s (C)-type mappings with fixed points, among others. We also give the corresponding characterizations for quasi-nonexpansive and some Suzuki’s (C)-type mappings with fixed points.